Counterion‐Directed, Structurally Tunable Assembly of Hydrogels, Membranes, and Sacs at Aqueous Liquid–Liquid Interfaces. Issue 5 (8th January 2016) - Wang, Yuefei; Qi, Wei; Huang, Renliang; Su, Rongxin; He, Zhimin
Abstract : Counterions play a crucial role in directing the self‐assembly of components in biological systems. In this paper, the self‐assembly of aromatic dipeptides and polysaccharide chitosan is reported at an aqueous liquid–liquid interface. It is shown that subtle modulations in the counterions and pH values allow changes in the self‐assembling pathway localized at the aqueous liquid–liquid interface and thus fabricate materials with distinct structural features and functions, from hydrogels to membranes and hollow sacs. The hydrogel shows strong birefringence and the directional freeze of the gel leads to the formation of macroscopically layered domains with sizes up to centimeters. Moreover, the membranes and sacs exhibit high mechanical strengths, tunable permeabilities, and pH‐responsiveness and have good performance for controlled release. Compared with other self‐assembling peptides, aromatic dipeptides are much smaller and easier to synthesize (low cost). The self‐assembly of these dipeptides with functional polysaccharide chitosan has potential applications in many areas, including large‐scale manufacture of microcapsules for controlled drug release and enzyme immobilization. Abstract : A counterion‐directed, structurally tunable assembly of hydrogels, robust membranes, and sacs at the interface between a dipeptide solution and a solution of polysaccharide chitosan is demonstrated. The formation of various materials arises from a competition between the reaction and diffusion of components at the aqueous liquid–liquid interface. The self‐assembled materials have great potential applications for controlled release.